Comparing flow cytometry with culture-based methods for microbial monitoring and as a diagnostic tool for assessing drinking water treatment processes - Cheswick, Ryan Ashley; Cartmell, Elise; Lee, Susan; Upton, Andrew; Weir, Paul; Moore, Graeme; Nocker, Andreas; Jefferson, Bruce; Jarvis, Peter (Elsevier, 2019)
Flow cytometry (FCM) and the ability to measure both total and intact cell populations through DNA staining methodologies has rapidly gained attention and consideration across the water sector in the past decade. In this study, water quality monitoring was undertaken over three years across 213 drinking water treatment works (WTW) in the Scottish Water region (Total n = 39,340). Samples subject to routine regulatory microbial analysis using culture-based methods were also analysed using FCM. In addition to final treated water, the bacterial content in raw water was measured over a one-year period. Three WTW were studied in further detail using on-site inter-stage sampling and analysis with FCM. It was demonstrated that there was no clear link between FCM data and the coliform samples taken for regulatory monitoring. The disinfectant Ct value (Ct = mg·min/L) was the driving factor in determining final water cell viability and the proportion of intact cells (intact/total cells) and the frequency of coliform detections in the water leaving the WTW. However, the free chlorine residual, without consideration of treatment time, was shown to have little impact on coliform detections or cell counts. Amongst the three treatment trains monitored in detail, the membrane filtration WTW showed the greatest log removal and robustness in terms of final water intact cell counts. Flow cytometry was shown to provide insights into the bacteriological quality of water that adds significant value over and above that provided by traditional bacterial monitoring.
Keywords: Flow cytometry; Disinfection; Drinking water; Bacteria